2009
DOI: 10.1097/tp.0b013e3181a75633
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Programmed Death-1 and Programmed Death-1 Ligand-1 Contributes to Testicular Immune Privilege

Abstract: The constitutive expression of PD-L1 in the testis is an important mechanism underlying testicular immune privilege and long-term survival of intratesticular islet allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 61 publications
(68 reference statements)
1
48
3
1
Order By: Relevance
“…Testicular tissue is an immunologically privileged site with naturally suppressed immune responses mediated by PD-1: PD-L1 negative co-stimulation [32]. The role of PD-L1 in testicular immune privilege and homeostasis of immune responses has been therefore clearly identified [32].…”
Section: Discussionmentioning
confidence: 99%
“…Testicular tissue is an immunologically privileged site with naturally suppressed immune responses mediated by PD-1: PD-L1 negative co-stimulation [32]. The role of PD-L1 in testicular immune privilege and homeostasis of immune responses has been therefore clearly identified [32].…”
Section: Discussionmentioning
confidence: 99%
“…76 It is constitutively expressed in the testis and involved in the survival of islet allografts, suggesting that the PD-1/PD-L1 system is a mechanism that underlies testicular immune privilege. 77 The growth arrest-specific gene 6 (Gas6)/Protein S (ProS)-Tyro3, Axl and Mer (TAM) system is a negative regulatory immune system. 78 We showed that TAM receptor tyrosine kinases and their common ligands, Gas6 and ProS, regulate immune homeostasis in the mouse testis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…PD-1 is expressed in T cells, and its activation by PD-L1 mediates T cell tolerance (Keir et al, 2006). An recent study demonstrated that PD-L1 is constitutively expressed in the testis and contributes to the long-term survival of islet allografts transplanted in the testis, suggesting that PD-1/PD-L1 system may represents a mechanism of testicular immune privilege (Cheng et al, 2009).…”
Section: Local Immunosuppression Mechanismsmentioning
confidence: 98%